2008
DOI: 10.1590/s0037-86822008000300016
|View full text |Cite
|
Sign up to set email alerts
|

Primeiro encontro de Lutzomyia longipalpis (Lutz & Neiva, 1912) na área urbana de Uberlândia, MG, concomitante com o relato de primeiro caso autóctone de leishmaniose visceral humana

Abstract: Relata-se a primeira ocorrência do vetor da leishmaniose visceral, Lutzomyia longipalpis, na área urbana de Uberlândia, estado de Minas Gerais e o primeiro caso de leishmaniose visceral humana autóctone no município, notificado ao Centro de Controle de Zoonoses, por meio da Vigilância Epidemiológica da Secretaria Municipal de Saúde. Discute-se a importância deste encontro na transmissão da doença nessa área.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 1 publication
0
11
0
3
Order By: Relevance
“…The complex comprises several ecotopes that favor the presence of sandflies. Moreover, it is close to two neighborhoods in the city where specimens of Lutzomyia longipalpis (Lutz & Neiva, 1912), a vector incriminated in the transmission of visceral leishmaniasis (VL), have been found and two cases of human VL have been recorded, showing that VL is an important public health problem in the municipality 17 . The objective of this study was to survey the sandfly fauna in the Parque do Sabiá complex and to evaluate the risk of transmission of leishmaniasis.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The complex comprises several ecotopes that favor the presence of sandflies. Moreover, it is close to two neighborhoods in the city where specimens of Lutzomyia longipalpis (Lutz & Neiva, 1912), a vector incriminated in the transmission of visceral leishmaniasis (VL), have been found and two cases of human VL have been recorded, showing that VL is an important public health problem in the municipality 17 . The objective of this study was to survey the sandfly fauna in the Parque do Sabiá complex and to evaluate the risk of transmission of leishmaniasis.…”
Section: Introductionmentioning
confidence: 78%
“…On the other hand, in 2008, a child was diagnosed with visceral leishmaniasis (VL), and subsequent epidemiological studies showed the autochthony of the case as well as the first record of the vector, Lutzomyia longipalpis, in the municipality 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Más allá de esto, la presencia de L. longipalpis en las proximidades de un centro urbano de la Costa Caribe de Colombia, reafirma la inclinación hacia la periurbanización de la especie en Latinoamérica (Oliveira et al 2000, Flórez et al 2006, Paula et al 2008, Rangel & Vilela 2008, lo cual se considera como uno de los factores determinantes del reciente incremento de los casos de leishmaniasis visceral en algunas regiones de Brasil (Oliveira et al 2006). Por lo anterior, las autoridades de salud locales no deben subestimar el riesgo epidemiológico que representa L. longipalpis, sino por el contrario motivarse a la toma de las medidas de control vectorial necesarias y a la caracterización de los potenciales sitios de cría e identificación de las especies arbóreas en las cuales se recolectó el material entomológico.…”
Section: Resultados Y Discusiónunclassified
“…The identification of phlebotomine sandfly fauna in the region showed the presence of transmitting vectors of ATL in environments with varying degrees of anthropization 19. In addition, in January 2008 the first case of human visceral leishmaniasis occurred in the urban area in a child six-months and 22 days old, born and raised in Uberlândia, who had no history of travel to areas where the transmission of AVL is endemic. Epidemiological investigations have confirmed the autochthony of the disease 23 . …”
Section: Leishmania (Viannia) Braziliensis L (V) Guyanensis L (Lmentioning
confidence: 88%